Efficacy and Safety of Fospropofol Disodium for Injection in General Anesthesia Induction for Adult Patients: A Phase 3 Trial - Wu, Chao-Meng; Zhang, Wen-Sheng; Liu, Jin; Zhang, Wei-Yi; Ke, Bo-Wen (Frontiers in Pharmacology, 2021)
Background: Fospropofol disodium for injection (FospropofolFD) is a prodrug that is metabolized into propofol to produce a general anesthesia effect when administered intravenously. Objective: This study aimed to assess the efficacy and safety of FospropofolFD in comparison with propofol medium/long-chain fat emulsion injections (propofol-MCT/LCT) for general anesthesia induction in adult patients undergoing elective surgeries. Setting: Nine academic medical centers in China. Method: This multicenter, randomized, double-blind, double-simulated, controlled, and non-inferiority trial evaluated 540 eligible adult patients randomly assigned (2:1) to the intervention (20 mg/kg FospropofolFD) or control (2 mg/kg propofol-MCT/LCT) groups. Main outcome measure: The primary efficacy endpoint was the success rate, defined as a Modified Observer’s Assessment of Alertness/Sedation Scale score of 1 within 5 min after study drug administration. The safety endpoints consisted of adverse events (AEs) related to consciousness, cognitive function, hemodynamic status, liver and kidney function, and blood tests. Results: A total of 347 (96.3%) and 175 (97.2%) patients in the intervention and control groups, respectively, completed the study. The success rate for the primary outcome was 97.7% for both study drugs. The most frequent AEs in the intervention group were abnormal feeling (62.0%), blood pressure reduction (13.5%), and injection site pain (13.3%). No AEs related to consciousness and mental and cognitive functions or serious adverse events were reported. Conclusion: FospropofolFD (20 mg/kg) is not inferior to propofol-MCT/LCT (2 mg/kg) in general anesthesia induction for American Society of Anesthesiologists (ASA) physical status I-II adult patients undergoing elective surgeries. It is safe and effective for clinical use under anesthesiologist monitoring. Impact on Practice Statement: FospropofolFD can produce a general anesthesia effect and reduce the incidence of pain at the site of injection.